PENGARUH TIME BUDGET PRESSURE, LOCUS OF CONTROL, DAN TASK COMPLEXITY PADA DYSFUNCTIONAL AUDIT BEHAVIOR AKUNTAN PUBLIK DI BALI - Dewi, Nia Riska; Wirasedana, Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
This study aims to examine the effects of time budget pressure, locus of control, and task complexity on dysfunctional audit behavior public accountant in Bali. By using nonprobability sampling technique, the data obtained through survey technique by distributing questionnaire to 75 auditors who worked at public accountant firms registered at Institut Akuntan Publik Indonesia (IAPI) Bali 2013. Multiple linear regression analysis used for this study. The results suggest that there were positive effect of time budget pressure, locus of control, and task complexity on dysfunctional audit behavior. Budget preparation time, individual characteristics, and auditor task complexity play a role in identifying auditor accepting of dysfunctional behavior. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: time budget pressure, locus of control, task complexity, dysfunctional audit behavior